2012
DOI: 10.1021/jp301671b
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Kinetics and Solubility of ZnO Nanoparticles Followed by AGNES

Abstract: There is a current debate on whether the toxicity of engineered ZnO nanoparticles (NPs) can be traced back to their nanoscale properties or rather to the simple fact of their relatively high solubility and consequent release of Zn2+ ions. In this work, the emerging electroanalytical technique AGNES (Absence of Gradients and Nernstian Equilibrium Stripping), which is specially designed to determine free metal ion concentration, is shown to be able to measure the Zn2+ concentration resulting from dissolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
180
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(196 citation statements)
references
References 46 publications
15
180
0
1
Order By: Relevance
“…The release of Zn 2+ by Nanosun and in-house synthesised ZnO particles has been studied in a previous paper. It has been shown that the extent of Zn 2+ release is dependent on the ZnO primary particle size [19,48]. This is commensurate with the classical predictions from the Kelvin equation relating solubility to the curvature of the particle.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The release of Zn 2+ by Nanosun and in-house synthesised ZnO particles has been studied in a previous paper. It has been shown that the extent of Zn 2+ release is dependent on the ZnO primary particle size [19,48]. This is commensurate with the classical predictions from the Kelvin equation relating solubility to the curvature of the particle.…”
Section: Resultssupporting
confidence: 72%
“…In contrast to SiO 2 which is amorphous, ZnO is crystalline and polar [18]. ZnO shows a tendency to dissolve in aqueous dispersion and release free Zn 2+ ion [19]. Finally ZnO nanoparticles have a strong tendency to aggregate [20,21].…”
mentioning
confidence: 99%
“…Experimental dissolution rate data in the specific water chemistry was obtained for each ENM and modeled using an assumed first-order rate process that proceeds until the equilibrium ion concentration is reached (Table S4). 105 Since there is no experimental data for dissolution of ENMs in freshwater and marine sediments, the rate of dissolution was assumed to be 1/10th the rate in the corresponding water column, considering mass transfer is slower in porous media. 66,68,106 Transfer of ENMs and suspended sediment from freshwater to coastal waters and the transfer from coastal waters to the marine compartment (out of the modeled system) is considered an advective flux, estimated using regional flow data (SIUG, Section 2.3.6).…”
Section: −99mentioning
confidence: 99%
“…[157] Uncoated ZnO NMs are also soluble in aqueous media (unlike TiO 2 NMs, and more so than Ag NMs) releasing Zn 2þ from the NM surface. [158,159] Although this offers further commercial applications of ZnO NMs, including better delivery of Zn 2þ as a nutritional supplement, [160] it can also be detrimental in aquatic environments because Zn 2þ is a well-characterised toxicant at higher concentrations in aquatic organisms, e.g. fish (see recent review by Hogstrand [161] ).…”
Section: Zinc Oxide Nmsmentioning
confidence: 99%
“…In suspensions, uncoated ZnO NMs aggregate, sediment and solubilise, and equilibrium Zn 2þ concentrations are affected by pH, particle size (especially where ZnO NM , 6 nm) and ionic strength of the media. [158,159] Toxicity in marine organisms has often been closely correlated with the concentration of released Zn 2þ . For example, cell growth inhibition (measured as decreased cell numbers and chlorophyll concentrations) of the marine phytoplankton Thalassiosira pseudonana exposed to ZnO NMs was closely correlated with the free Zn 2þ concentration in suspension.…”
Section: Zinc Oxide Nmsmentioning
confidence: 99%